Proposing an Efficient CNN-Based Architecture for Image Processing - Ferreira, Verner Rafael; Canuto, Anne Magaly de Paula (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2025)
This paper introduces the Defiber layer, a Convolutional Neural Network (CNN) architecture component that systematically reduces input size during the convolution phase. In order to assess the feasibility of the proposed model, an empirical analysis was conducted using two image datasets: the CIFAR-10 dataset and an additional in-house dataset. Aiming to provide a comprehensive comparison, several existing CNN architectures are also included in this empirical analysis. The models are assessed based on accuracy and hardware performance criteria, including inference time and throughput. Our model surpasses expectations, outperforming some of the other evaluated models, both deep and mobile. Notably, the Defiber layer demonstrates remarkable effectiveness and consistent results during performance tests.